What determines the export performance? : A comparative analysis of China and India in the European Union - Coutinho, Ana Luísa (2012)
This paper aims to assess the competitiveness of exports of manufactured goods from China and India to the European Union in the 2000s. The empirical analysis is based on two methodologies: (i) a Constant Market Share analysis which allows to decompose the export growth to the European market into several components including an effect usually related to competitiveness, and (ii) an analysis based on the combination of revealed comparative advantage indexes with a geographic orientation of trade which allows to identify the products of China and India that appear to have export potential.